'With sound of lute and pleasing words': The Lute Song and Voice Types in Late Sixteenth- and Early Seventeenth-Century England. Issue 1 (April 2021) - Robinson, Richard
Abstract: The Elizabethan and Jacobean lute song (1597–1622) represents one of the most iconic genres of all early music. Although much literature has been dedicated to this repertory, the issue of the voices for which this music was probably intended still remains surprisingly underexplored. This subject has, moreover, acquired greater significance in light of research undertaken by Simon Ravens (2014) and Andrew Parrott (2015), which has challenged the plausibility of the falsetto voice in Medieval and Renaissance Europe, particularly in sacred music. This paper explores the issue of the types of voices that most likely performed the Elizabethan and Jacobean lute song in three ways. Firstly, contemporary English evidence for lutes and viols is analyzed together with information regarding tuning and transposition. Secondly, the music itself is investigated, including the part names and clefs used alongside the tessitura of the melodic line. Finally, a detailed examination of evidence for the tenor and falsetto voice is presented, including a critical examination of the word 'faine' (usually assumed to mean 'falsetto'). The collective results are then brought together to refine current ideas regarding the voices used in the Elizabethan and Jacobean lute song.